(Meth) Acrylic Resin Composition, Film, And Polarizing Plate

By adding elastomer and antioxidant to the (meth)acrylic resin composition, the problem of the resin composition being prone to deterioration under thermal load is solved, and the heat resistance of the resin composition is improved, ensuring the stable performance of the film at high temperatures.

CN119894978APending Publication Date: 2025-04-25SUMITOMO CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380070281.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-14
Filing Date
2023-09-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When the film is made from the (meth)acrylic resin composition, the resin composition is prone to deterioration due to thermal load, which affects the heat resistance of the film.

Method used

By adding elastomer components and antioxidants to the (meth)acrylic resin composition, a specific resin composition is formed, ensuring that the mass reduction rate of the resin composition is less than 60% at high temperatures.

Benefits of technology

The (meth)acrylic resin composition has excellent heat resistance and can maintain stable performance during long-term heating of 270°C or above or above.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

Provided are: a (meth) acrylic resin composition having excellent heat resistance; a film formed from the same; and a polarizing plate comprising the film. Provided are: a (meth) acrylic resin composition containing a (meth) acrylic resin (A), an elastomer component (B), and an antioxidant (C), the mass ratio of the content of the antioxidant (C) to the content of the elastomer component (B) being 0.006-0.2 (inclusive);
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a (meth)acrylic resin composition, a film formed therefrom, and a polarizing plate. Background Art

[0002] Polarizing plates widely used in image display devices such as liquid crystal display devices and organic EL display devices generally have a structure in which a thermoplastic resin film is laminated on one or both sides of a polarizer as a protective film. Japanese Patent Application Laid-Open No. 2008-102274 (Patent Document 1) discloses that an acrylic resin film can be used as a protective film.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2008-102274 Summary of the invention

[0006] Problems to be solved by the invention

[0007] When a (meth)acrylic resin film is produced from a (meth)acrylic resin composition, a heat load is applied to the (meth)acrylic resin composition through a film forming step and, if necessary, a stretching step. Therefore, it is required that the (meth)acrylic resin composition is not easily degraded by the heat load.

[0008] An object of the present invention is to provide a (meth)acrylic resin composition having excellent heat resistance, a film formed therefrom, and a polarizing plate including the film.

[0009] Means for solving problems

[0010] The present invention provides the (meth)acrylic resin composition, film, and polarizing plate shown below.

[0011] [1] A (meth)acrylic resin composition comprising a (meth)acrylic resin (A), an elastomer component (B) and an antioxidant (C),

[0012] The mass ratio of the content of the antioxidant (C) to the content of the elastomer component (B) is 0.006 or more and 0.2 or less.

[0013] [2] The (meth)acrylic resin composition according to [1], wherein the content of the elastomer component (B) is 17.5 parts by mass or more based on 100 parts by mass of the (meth)acrylic resin (A).

[0014] [3] The (meth)acrylic resin composition according to [1] or [2], wherein the content of the antioxidant (C) is 0.4 parts by mass or more and 3.5 parts by mass or less based on 100 parts by mass of the (meth)acrylic resin (A).

[0015] [4] The (meth)acrylic resin composition according to any one of [1] to [3], wherein the mass reduction rate when heated at a temperature of 270°C to 275°C in an air atmosphere for 3 hours, or when heated at a temperature of 250°C to 255°C in an air atmosphere for 6 hours is 60% or less.

[0016] [5] The (meth)acrylic resin composition according to any one of [1] to [4], wherein the elastomer component (B) is rubber particles.

[0017] [6] The (meth)acrylic resin composition according to any one of [1] to [5], wherein the (meth)acrylic resin (A) comprises a (meth)acrylic resin (A-1) and a (meth)acrylic resin (A-2) having syndiotacticities different from each other.

[0018] [7] The (meth)acrylic resin composition according to any one of [1] to [6], which is in the form of pellets.

[0019] [8] A film formed from the (meth)acrylic resin composition according to any one of [1] to [7].

[0020] [9] A polarizing plate comprising a polarizer, an adhesive layer, and the film described in [8] in this order.

[0021] Effects of the Invention

[0022] The present invention can provide a (meth)acrylic resin composition having excellent heat resistance, a film formed therefrom, and a polarizing plate including the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic cross-sectional view showing an example of the layer structure of the polarizing plate of the present invention.

[0024] Figure 2 This is a schematic cross-sectional view showing another example of the layer structure of the polarizing plate of the present invention. DETAILED DESCRIPTION

[0025] <(Meth)acrylic resin composition>

[0026] The (meth)acrylic resin composition of the present invention (hereinafter, also referred to as "(meth)acrylic resin composition") comprises a (meth)acrylic resin (A), an elastomer component (B), and an antioxidant (C). Hereinafter, the (meth)acrylic resin (A), the elastomer component (B), and the antioxidant (C) are also referred to as "component (A)", "component (B)", and "component (C)", respectively.

[0027] In the present specification, "(meth)acrylic" means at least one selected from acrylic and methacrylic groups. The same applies to expressions such as "(meth)acryloyl" and "(meth)acrylate".

[0028] [1] (Meth) acrylic resin (A)

[0029] Component (A) is a thermoplastic (meth)acrylic resin. Component (A) may include a (meth)acrylic resin (A-1) and a (meth)acrylic resin (A-2) having different syndiotacticity. Hereinafter, (meth)acrylic resin (A-1) and (meth)acrylic resin (A-2) are also referred to as "component (A-1)" and "component (A-2)", respectively. The syndiotacticity of component (A-1) is higher than that of component (A-2). Alternatively, component (A) may also include one (meth)acrylic resin (e.g., component (A-1) or component (A-2)).

[0030] Component (A-1) is preferably a polymer containing methacrylate as a main monomer (containing 50% by mass or more). Component (A-1) may be a homopolymer of methacrylate or a copolymer of methacrylate and other copolymerization components.

[0031] The content of the structural unit derived from methacrylate in component (A-1) is preferably 90% by mass or more, more preferably 95% by mass or more, further preferably 98% by mass or more, further preferably 99% by mass or more, and particularly preferably 100% by mass.

[0032] In a preferred embodiment, the component (A-1) is a homopolymer of methacrylate. In another preferred embodiment, the component (A-1) is a homopolymer of methyl methacrylate.

[0033] Examples of the methacrylate include methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, benzyl methacrylate, 2-ethylhexyl methacrylate, and 2-hydroxyethyl methacrylate. Component (A-1) may include one or more structural units derived from methacrylate.

[0034] The methacrylate preferably comprises methyl methacrylate, and more preferably methyl methacrylate.

[0035] Examples of the other copolymerization components include:

[0036] Acrylates such as ethyl acrylate, n-butyl acrylate, isobutyl acrylate or tert-butyl acrylate, cyclohexyl acrylate, phenyl acrylate, benzyl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, etc.;

[0037] Hydroxyalkyl acrylates such as methyl 2-(hydroxymethyl)acrylate, methyl 2-(1-hydroxyethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, isobutyl 2-(hydroxymethyl)acrylate or tert-butyl 2-(hydroxymethyl)acrylate;

[0038] Unsaturated acids such as methacrylic acid and acrylic acid;

[0039] Halogenated styrenes such as chlorostyrene and bromostyrene;

[0040] Substituted styrenes such as vinyltoluene and α-methylstyrene;

[0041] Unsaturated nitriles such as acrylonitrile and methacrylonitrile;

[0042] Unsaturated anhydrides such as maleic anhydride and citraconic anhydride;

[0043] Monofunctional monomers such as unsaturated imides such as phenylmaleimide and cyclohexylmaleimide.

[0044] The above other monofunctional monomers may be used alone or in combination of two or more.

[0045] As the other copolymerization components, a polyfunctional monomer may also be used.

[0046] Examples of the polyfunctional monomer include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, tetradecaethylene glycol di(meth)acrylate, and the like, which are obtained by esterifying both terminal hydroxyl groups of ethylene glycol or its oligomers with (meth)acrylic acid;

[0047] A substance obtained by esterifying both terminal hydroxyl groups of propylene glycol or its oligomers with (meth)acrylic acid;

[0048] Those obtained by esterifying the hydroxyl group of a diol with (meth)acrylic acid, such as neopentyl glycol di(meth)acrylate, hexanediol di(meth)acrylate, and butanediol di(meth)acrylate;

[0049] A product obtained by esterifying both terminal hydroxyl groups of bisphenol A, an alkylene oxide adduct of bisphenol A, or a halogen-substituted product thereof with (meth)acrylic acid;

[0050] Those obtained by esterifying a polyol such as trimethylolpropane or pentaerythritol with (meth)acrylic acid, and those obtained by ring-opening addition of epoxy groups of glycidyl (meth)acrylate to their terminal hydroxyl groups;

[0051] Those obtained by ring-opening addition of the epoxy group of glycidyl (meth)acrylate to dibasic acids such as succinic acid, adipic acid, terephthalic acid, phthalic acid, halogen-substituted products thereof, or alkylene oxide adducts thereof;

[0052] (Meth) aryl acrylate; aromatic divinyl compounds such as divinylbenzene, etc.

[0053] The weight average molecular weight Mw of the component (A-1) is, for example, 40,000 or more and 150,000 or less. From the viewpoint of heat resistance of a film formed from the (meth)acrylic resin composition and formability into a film, it is preferably 40,000 or more and 120,000 or less, and more preferably 50,000 or more and 100,000 or less.

[0054] The molecular weight distribution (weight average molecular weight Mw / number average molecular weight Mn) of the component (A-1) is, for example, 1.01 or more and 1.8 or less, and is preferably 1.03 or more and 1.5 or less, and more preferably 1.05 or more and 1.3 or less from the viewpoint of heat resistance of a film formed from the (meth)acrylic resin composition. Mw and Mn can be controlled by adjusting the type and / or amount of the polymerization initiator used in the preparation of the component (A-1). Mw and Mn are measured by gel permeation chromatography (GPC) (standard polystyrene conversion).

[0055] From the viewpoint of improving the toughness of a film formed from the (meth)acrylic resin composition, the glass transition temperature Tg of the component (A-1) is preferably 110° C. to 160° C., more preferably 120° C. to 150° C., and even more preferably 125° C. to 140° C. Tg can be controlled by adjusting the molecular weight, syndiotacticity, copolymer components, and the like.

[0056] The syndiotacticity (rr) of the component (A-1) in terms of triads is, for example, 50% or more, preferably 55% or more, more preferably 60% or more, further preferably 65% ​​or more, and further preferably 70% or more, from the viewpoint of improving the toughness and heat resistance of a film formed from the (meth)acrylic resin composition. The syndiotacticity (rr) of the component (A-1) in terms of triads is usually 90% or less, and may be 85% or less.

[0057] The syndiotacticity (rr) based on triads is the ratio of two chains (diads) of a chain of three consecutive structural units (triads) that are both racemic (expressed as rr). The syndiotacticity (rr) (%) based on triads is calculated as follows: 1 The H-NMR spectrum was calculated by measuring the area (X) of the 0.6 to 0.95 ppm region and the area (Y) of the 0.6 to 1.35 ppm region when the internal standard TMS was set to 0 ppm based on the spectrum, and (X / Y)×100.

[0058] The component (A-1) having a syndiotacticity (rr) in terms of triad within the above range can be adjusted, for example, according to the method described in International Publication No. 2016 / 080124. The ratio of the syndiotacticity (rr) in terms of triad can be increased by lowering the polymerization temperature or extending the polymerization time.

[0059] Component (A-2) may be, for example, a polymer containing methacrylate as a main monomer (containing 50% by mass or more), preferably a copolymer of methacrylate and other copolymerization components. In a preferred embodiment, component (A-2) is a copolymer containing a structural unit derived from methyl methacrylate. In another preferred embodiment, component (A-2) is a copolymer containing a structural unit derived from methyl methacrylate and a structural unit derived from methyl acrylate.

[0060] Examples of other copolymerization components other than methyl acrylate include those exemplified as methacrylic acid ester and other copolymerization components in component (A-1).

[0061] The weight average molecular weight Mw of the component (A-2) is, for example, 40,000 or more and 150,000 or less, preferably 40,000 or more and 130,000 or less, and more preferably 50,000 or more and 120,000 or less, from the viewpoint of heat resistance of a film formed from the (meth)acrylic resin composition and formability into a film.

[0062] The molecular weight distribution (weight average molecular weight Mw / number average molecular weight Mn) of the component (A-2) is, for example, 1.01 or more and 3.0 or less. From the viewpoint of heat resistance of a film formed from the (meth)acrylic resin composition, it is preferably 1.03 or more and 2.8 or less, and more preferably 1.05 or more and 2.7 or less. Mw and Mn can be controlled by adjusting the type and / or amount of the polymerization initiator used in the preparation of the component (A-2). Mw and Mn are measured by gel permeation chromatography (GPC) (standard polystyrene conversion).

[0063] The glass transition temperature Tg of component (A-2) is preferably 80° C. to 140° C., more preferably 90° C. to 130° C., and even more preferably 90° C. to less than 125° C. Tg can be controlled by adjusting the molecular weight, syndiotacticity, copolymer components, and the like.

[0064] The syndiotacticity (rr) of the component (A-2) in terms of triad is, for example, 25% to 60%, preferably 30% to 55%, and more preferably 40% to 54%.

[0065] Component (A-2) can be prepared by referring to the method described in, for example, JP-A-2009-145397 and JP-A-2021-155698. Component (A-2) can be prepared by radical polymerization.

[0066] The (meth)acrylic resin composition may contain resin components other than the component (A), but from the viewpoint of heat resistance of a film formed from the (meth)acrylic resin composition, the content of the component (A) in the resin components (excluding the component (B)) contained in the (meth)acrylic resin composition is preferably high, and the content is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, further preferably 99% by mass or more, and particularly preferably 100% by mass.

[0067] When the content of component (A-1) is A1 (parts by mass) and the content of component (A-2) is A2 (parts by mass), A2 is preferably larger than A1 from the viewpoint of improving the toughness of a film formed from the (meth)acrylic resin composition. The (meth)acrylic resin composition more preferably satisfies the following formula:

[0068] 0≤A1 / (A1+A2)<0.5.

[0069] Satisfying this formula is advantageous in improving the toughness. A1 / (A1+A2) is preferably 0.40 or less, more preferably 0.35 or less, and even more preferably 0.30 or less.

[0070] [2] Elastomer component (B)

[0071] The (meth)acrylic resin composition contains a component (B). Inclusion of the component (B) is advantageous in improving the toughness of a film formed from the (meth)acrylic resin composition. Examples of the component (B) include rubber particles.

[0072] The rubber particles are rubber elastic particles including a layer showing rubber elasticity. The rubber particles may be particles consisting only of a layer showing rubber elasticity (rubber elastic layer), or particles having a multilayer structure of a layer showing rubber elasticity and other layers, preferably particles of the multilayer structure. The layer showing rubber elasticity includes a rubber elastomer. Examples of the rubber elastomer include olefin elastic polymers, diene elastic polymers, styrene-diene elastic copolymers, acrylic elastic polymers, and the like. Among them, from the viewpoint of light resistance and transparency of the film formed by the (meth) acrylic resin composition, acrylic elastic polymers are preferably used.

[0073] The acrylic elastic polymer may be a polymer mainly composed of an alkyl acrylate, that is, a polymer containing 50% by mass or more of a structural unit derived from an alkyl acrylate based on the total monomer amount. The acrylic elastic polymer may be a homopolymer of an alkyl acrylate, or a copolymer containing 50% by mass or more of a structural unit derived from an alkyl acrylate and 50% by mass or less of a structural unit derived from other polymerizable monomers.

[0074] As the acrylic acid alkyl ester constituting the acrylic elastic polymer, an acrylic acid alkyl ester having an alkyl group with 4 to 8 carbon atoms is generally used.

[0075] Examples of the other polymerizable monomers include alkyl methacrylates such as methyl methacrylate and ethyl methacrylate; styrene-based monomers such as styrene and alkyl styrene; monofunctional monomers such as unsaturated nitriles such as acrylonitrile and methacrylonitrile; alkenyl esters of unsaturated carboxylic acids such as allyl (meth)acrylate and methallyl (meth)acrylate; diene esters of dibasic acids such as diallyl maleate; and polyfunctional monomers such as unsaturated carboxylic acid diesters of diols such as alkylene glycol di(meth)acrylate.

[0076] The rubber particles containing an acrylic elastic polymer are preferably particles having a multilayer structure of a layer of an acrylic elastic polymer. Specifically, particles having a two-layer structure having a hard polymer layer mainly composed of an alkyl methacrylate on the outside of the layer of the acrylic elastic polymer, and particles having a three-layer structure having a hard polymer layer mainly composed of an alkyl methacrylate on the inside of the layer of the acrylic elastic polymer are exemplified. The alkyl methacrylate is preferably methyl methacrylate.

[0077] The rubber particles preferably have an average particle size of 10 nm or more and 350 nm or less up to the rubber elastic body layer (acrylic elastic polymer layer) contained therein. The average particle size in this range is advantageous in improving the toughness of the optical film and the adhesion to the polarizer. The average particle size is more preferably 30 nm or more, more preferably 50 nm or more, more preferably 320 nm or less, and more preferably 300 nm or less.

[0078] The average particle size of the rubber particles up to the rubber elastic body layer (layer of acrylic elastic polymer) can be measured as follows. That is, if such rubber particles are mixed into a (meth) acrylic resin and filmed, and the cross section is stained with an aqueous solution of ruthenium oxide, only the rubber elastic body layer is colored and observed to be roughly circular, and the (meth) acrylic resin of the parent layer is not stained. Therefore, a slice is prepared from the cross section of the film after such dyeing using a slicer, and it is observed with an electron microscope. Then, 100 dyed rubber particles are randomly selected, and the particle size (diameter up to the rubber elastic body layer) of each is calculated, and the number average value is used as the above average particle size. Since the measurement is performed using such a method, the above average particle size obtained is the number average particle size.

[0079] In the case of a rubber particle whose outermost layer is a hard polymer mainly composed of methyl methacrylate and in which a rubber elastic body layer (a layer of acrylic elastic polymer) is enclosed, if it is mixed into the (meth) acrylic resin of the matrix, the outermost layer of the rubber particle is mixed with the (meth) acrylic resin of the matrix. Therefore, if the cross section is stained with ruthenium oxide and observed with an electron microscope, the rubber particle is observed as a particle with the outermost layer removed. Specifically, in the case of a rubber particle with a two-layer structure in which the inner layer is an acrylic elastic polymer and the outer layer is a hard polymer mainly composed of methyl methacrylate, the acrylic elastic polymer part of the inner layer is stained and observed as a particle with a single-layer structure. In addition, in the case of a rubber particle with a three-layer structure in which the innermost layer is a hard polymer mainly composed of methyl methacrylate, the middle layer is an acrylic elastic polymer, and the outermost layer is a hard polymer mainly composed of methyl methacrylate, it is observed as a particle with a two-layer structure in which the center part of the innermost particle is not stained and only the acrylic elastic polymer part of the middle layer is stained.

[0080] The content of component (B) is preferably 17.5 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 24 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic resin (A), from the viewpoint of improving the toughness of a film formed from the (meth)acrylic resin composition. The content is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 60 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic resin (A), from the viewpoint of the elastic modulus of a film formed from the (meth)acrylic resin composition.

[0081] From the viewpoint of improving the toughness of a film formed from the (meth)acrylic resin composition, the mass ratio of the content of the component (B) to the content of the (meth)acrylic resin (A) is preferably 0.175 or more, more preferably 0.20 or more, and even more preferably 0.24 or more. From the viewpoint of the elastic modulus of a film formed from the (meth)acrylic resin composition, the mass ratio is preferably 0.80 or less, more preferably 0.70 or less, and even more preferably 0.60 or less.

[0082] [3] Antioxidants (C)

[0083] The (meth)acrylic resin composition contains a component (C). The content of the component (C) is such that the mass ratio of the content of the component (C) to the content of the elastomer component (B) is 0.006 or more and 0.2 or less. By containing the component (C) in such a predetermined amount, the (meth)acrylic resin composition and the film formed therefrom exhibit excellent heat resistance.

[0084] From the viewpoint of improving the heat resistance of the (meth)acrylic resin composition and the film, the mass ratio is preferably 0.007 or more, more preferably 0.010 or more, further preferably 0.015 or more, further preferably 0.020 or more, particularly preferably 0.022 or more.

[0085] If the mass ratio is too large, component (C) may bleed out of a film formed from the (meth)acrylic resin composition when the film is used. Therefore, the mass ratio is 0.20 or less, preferably 0.18 or less, more preferably 0.16 or less, further preferably 0.14 or less, and further preferably 0.12 or less.

[0086] The content of the component (C) is preferably 0.4 parts by mass or more, more preferably 0.45 parts by mass or more, further preferably 0.5 parts by mass or more, and further preferably 0.55 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic resin (A), from the viewpoint of improving the heat resistance of the film formed from the (meth)acrylic resin composition. The content is preferably 5.0 parts by mass or less, more preferably 4.5 parts by mass or less, further preferably 4.0 parts by mass or less, and further preferably 3.5 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic resin (A), from the viewpoint of preventing the component (C) from seeping out of the film formed from the (meth)acrylic resin composition.

[0087] From the viewpoint of improving the heat resistance of the film formed from the (meth)acrylic resin composition, the mass ratio of the content of the component (C) to the content of the (meth)acrylic resin (A) is preferably 0.004 or more, more preferably 0.0045 or more, further preferably 0.005 or more, and further preferably 0.0055 or more. From the viewpoint of preventing the component (C) from seeping out of the film formed from the (meth)acrylic resin composition, the mass ratio is preferably 0.05 or less, more preferably 0.045 or less, further preferably 0.04 or less, and further preferably 0.035 or less.

[0088] Component (C) may be a primary antioxidant, a secondary antioxidant, or a combination thereof. As a primary antioxidant, for example, a phenolic antioxidant or an amine antioxidant may be used, and as a secondary antioxidant, for example, a phosphorus antioxidant or a sulfur antioxidant may be used. In addition, as component (C), a phosphorus / phenol composite antioxidant may be used. A phosphorus / phenol composite antioxidant is a compound having one or more phosphorus atoms and a phenol structure in each molecule, and has the functions of both a primary antioxidant and a secondary antioxidant. Two or more components (C) may be used in combination.

[0089] Examples of the phenolic antioxidant include Irganox (registered trademark) 1010 (Irganox 1010: pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], manufactured by BASF Corporation), Irganox 1076 (Irganox 1076: octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, manufactured by BASF Corporation), Irganox 1330 (Irganox 1330: 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, manufactured by BASF Corporation), and Irganox 3114 (Irganox 3114: 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF Corporation), Irganox 3790 (Irganox 3790: 1,3,5-tris((4-tert-butyl-3-hydroxy-2,6-xylyl)methyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF Corporation), Irganox 1035 (Irganox 1035: thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], manufactured by BASF Corporation), Irganox 1135 (Irganox 1135: 3,5-bis(1,1-dimethylethyl)-4-hydroxy-C7-C9 side chain alkyl ester of phenylpropionic acid, manufactured by BASF Corporation), Irganox 1520L (Irganox 1520L: 4,6-bis(octylthiomethyl)-o-cresol, manufactured by BASF Corporation), Irganox 3125 (Irganox 3125, manufactured by BASF Corporation), Irganox 565 (Irganox 565: 2,4-bis(n-octylthio)-6-(4-hydroxy-3',5'-di-tert-butylanilino)-1,3,5-triazine, manufactured by BASF Corporation), ADK STAB (registered trademark) AO-80 (ADK STAB AO-80: 3,9-bis(2-(3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy)-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5,5)undecane, manufactured by ADEKA Co., Ltd.), Sumilizer (registered trademark) BHT, Sumilizer GA-80, Sumilizer GS (all manufactured by Sumitomo Chemical Co., Ltd.), Cyanox (registered trademark) 1790 (Cyanox 1790, manufactured by Cytec Co., Ltd.), vitamin E (manufactured by Eisai Co., Ltd.), etc.

[0090] Examples of the amine antioxidant include Sumilizer (registered trademark) BPA (N,N′-di-sec-butyl-p-phenylenediamine), Sumilizer (registered trademark) BPA-M1, Sumilizer (registered trademark) 4ML (p-phenylenediamine derivative), and Sumilizer (registered trademark) 9A (alkylated diphenylamine).

[0091] Examples of the phosphorus-based antioxidant include Irgafos (registered trademark) 168 (Irgafos 168: tris(2,4-di-tert-butylphenyl)phosphite, manufactured by BASF Corporation), Irganox 12 (Irgafos 12: tris[2-[[2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphin-6-yl]oxy]ethyl]amine, manufactured by BASF Corporation), Irgafos 38 (Irgafos 38: bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl phosphite, manufactured by BASF Corporation), ADK STAB (registered trademark) 329K, ADK STAB PEP36, and ADK STAB PEP-8 (all manufactured by ADEKA Corporation), and Sandstab P-EPQ (manufactured by Clariant), Weston (registered trademark) 618, Weston 619G (all manufactured by GE), Ultranox 626 (manufactured by GE), etc.

[0092] Examples of the phosphorus / phenol composite antioxidant include Sumilizer (registered trademark) GP (6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1.3.2]dioxaphosphopepene) (manufactured by Sumitomo Chemical Co., Ltd.).

[0093] Examples of the sulfur-based antioxidant include dialkyl thiodipropionate compounds such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate, and β-alkylmercaptopropionate compounds of polyhydric alcohols such as tetrakis[methylene(3-dodecylthio)propionate]methane.

[0094] From the viewpoint of improving the heat resistance of the film formed from the (meth)acrylic resin composition, component (C) is preferably a combination of a primary antioxidant and a secondary antioxidant, and more preferably a combination of a phenolic antioxidant and a phosphorus antioxidant. When a secondary antioxidant (preferably a phosphorus antioxidant) and a primary antioxidant (preferably a phenolic antioxidant) are used in combination, the content of the secondary antioxidant (preferably a phosphorus antioxidant) in the (meth)acrylic resin composition: the content of the primary antioxidant (preferably a phenolic antioxidant) is preferably 1:5 to 2:1, more preferably 1:2 to 2:1 in terms of mass ratio.

[0095] It should be noted that the (meth)acrylic resin composition may contain other components besides the above as necessary, such as lubricants, anti-blocking agents, heat stabilizers, ultraviolet absorbers, antistatic agents, impact resistance improvers, surfactants, release agents, etc.

[0096] By including a UV absorber, degradation of the (meth)acrylic resin composition and a film formed therefrom due to UV rays can be suppressed. In addition, by including a UV absorber, the generation of gel when a heat load is applied to a film formed from the (meth)acrylic resin composition can be suppressed.

[0097] Examples of the ultraviolet absorber include oxybenzophenone compounds, benzotriazole compounds, salicylate compounds, benzophenone compounds, cyanoacrylate compounds, nickel complex salt compounds, etc. Among them, benzotriazole compounds are preferred from the viewpoint of suppressing gel formation.

[0098] When a UV absorber is added, the amount thereof is usually 1 part by mass or more, preferably 1.5 parts by mass or more, and usually 3 parts by mass or less, preferably 2.5 parts by mass or less, based on 100 parts by mass of the (meth)acrylic resin (A).

[0099] [4] Shape of (meth)acrylic resin composition

[0100] The (meth)acrylic resin composition may be in a solid state or in a liquid state. In the case of a solid state, the shape of the (meth)acrylic resin composition is not particularly limited, and examples thereof include amorphous, granular, pelletized, and granular shapes. When the (meth)acrylic resin composition is used for forming such as film forming, the (meth)acrylic resin composition is preferably in a pelletized shape.

[0101] [5] Heat resistance of (meth)acrylic resin compositions

[0102] The (meth)acrylic resin composition can have excellent heat resistance. The (meth)acrylic resin composition having excellent heat resistance preferably has a mass reduction rate of 60% or less when subjected to heating test I (heating at a temperature of 270° C. to 275° C. for 3 hours in an air atmosphere) or heating test II (heating at a temperature of 250° C. to 255° C. for 6 hours in an air atmosphere).

[0103] The mass reduction rate during the heating test can be measured by the method shown in the following [Example]. The mass reduction rate during the heating test I or II is more preferably 55% or less, further preferably 50% or less, further preferably 45% or less, particularly preferably 40% or less, further particularly preferably 35% or less, further particularly preferably 30% or less, and most preferably 25% or less. It can further show a mass reduction rate of 20% or less, and further can show a mass reduction rate of 15% or less. The mass reduction rate is usually 1% or more.

[0104] The IR intensity ratio of the (meth) acrylic resin composition having excellent heat resistance in the heating test I or II is preferably 0.070 or less, more preferably 0.065 or less, further preferably 0.060 or less, further preferably 0.050 or less, particularly preferably 0.040 or less, and most preferably 0.030 or less. The IR intensity ratio is usually 0.005 or more. More specifically, the IR intensity ratio is measured and calculated according to the method shown in the following [Example]. Wave number 1725cm -1 The peak intensity at a refers to the signal intensity value at that wave number.

[0105] In the IR spectrum of the (meth)acrylic resin composition after the heating test, the wave number 1725 cm -1 The peak at is derived from the carbonyl group of the carboxylate group or carboxyl group of the monomer units constituting component (A) and component (B). Wave number 1785±5cm -1 The signal at is a signal from the acid anhydride group contained in the gel generated by the heat load of the heating test. It is considered that the larger the IR intensity ratio is, the more gel is generated in the (meth)acrylic resin composition, and the IR intensity ratio can be an indicator of the heat resistance (gel generation inhibition) of the (meth)acrylic resin composition.

[0106] <Film>

[0107] The (meth) acrylic resin composition is subjected to film forming and further subjected to stretching treatment as required, thereby obtaining a (meth) acrylic resin film. The (meth) acrylic resin film comprises components (A), (B) and (C). The (meth) acrylic resin film can be suitably used as an optical film, such as a protective film for a polarizing plate. The (meth) acrylic resin film can be an unstretched film or any one of a uniaxially or biaxially stretched film. Biaxial stretching can be biaxial stretching in which stretching is performed simultaneously in two stretching directions, or can be sequential biaxial stretching in which stretching is performed in a first direction and then in a second direction different from the first direction.

[0108] The thickness of the film is usually 5 μm or more and 200 μm or less, preferably 10 μm or more and 120 μm or less, more preferably 10 μm or more and 85 μm or less, and further preferably 15 μm or more and 65 μm or less. The thickness of the film may be 60 μm or less, or 50 μm or less. Reducing the thickness of the film is beneficial for thinning the polarizing plate including the film and the image display device using the film.

[0109] The (meth) acrylic resin film may have a surface treatment layer (coating layer) on one or both sides. As the surface treatment layer, a hard coating layer, an anti-glare layer, an anti-reflection layer, a light diffusion layer, an antistatic layer, an antifouling layer, a conductive layer, etc. may be cited, preferably a hard coating layer. As the surface treatment layer, a cured layer of a curable resin composition containing an active energy ray curable compound may be cited. The active energy ray curable compound is a compound that is polymerized and cured by irradiation with active energy rays such as ultraviolet rays and electron beams. As the active energy ray curable compound, for example, a monofunctional, difunctional or trifunctional or higher (meth) acrylate compound may be cited. One or more active energy ray curable compounds may be used.

[0110] The thickness of the surface treatment layer such as the hard coat layer is, for example, 0.1 μm to 50 μm, preferably 0.5 μm to 30 μm, more preferably 1 μm to 20 μm, further preferably 1 μm to 10 μm.

[0111] <Polarizing plate>

[0112] In this specification, "polarizing plate" refers to an optical laminate comprising a polarizer and a thermoplastic resin film laminated on one or both sides thereof. In the polarizing plate, the polarizer and the thermoplastic resin film are laminated via an adhesive layer. The adhesive layer is a layer formed of an adhesive composition, for example, a cured layer of the adhesive composition.

[0113] The polarizing plate may include films or layers other than the polarizer and the above-mentioned thermoplastic resin film.

[0114] The polarizing plate of the present invention comprises a polarizer, an adhesive layer and the above-mentioned (meth) acrylic resin film as a thermoplastic resin film in sequence. The (meth) acrylic resin film is a film formed by the (meth) acrylic resin composition of the present invention. Usually, the polarizer is in contact with the adhesive layer, and the adhesive layer is in contact with the (meth) acrylic resin film. Since the polarizing plate of the present invention uses the (meth) acrylic resin film of the present invention as a protective film for the polarizer, the adhesion between the polarizer and the (meth) acrylic resin film can become good, thereby, the durability of the polarizing plate can be made good. The polarizing plate of the present invention can be suitably used in image display devices such as liquid crystal display devices and organic EL devices.

[0115] [1] Structure of polarizing plate

[0116] Examples of the layer constitution of the polarizing plate of the present invention are shown in Figure 1 and Figure 2 .

[0117] like Figure 1 As shown, the polarizing plate of the present invention may include a polarizer 30, a first adhesive layer 15, and a first thermoplastic resin film 10 which is the (meth) acrylic resin film of the present invention in this order, that is, it may include a polarizer 30 and a first thermoplastic resin film 10 laminated and bonded on one surface thereof via the first adhesive layer 15.

[0118] A primer layer may be interposed between the first adhesive layer 15 and the first thermoplastic resin film 10, or the first adhesive layer 15 may be in direct contact with the first thermoplastic resin film 10. The polarizer 30 and the first adhesive layer 15 are preferably in direct contact with each other.

[0119] In addition, if Figure 2 As shown, the polarizing plate of the present invention may also include a polarizer 30, a first thermoplastic resin film 10 as the (meth) acrylic resin film of the present invention laminated and bonded to one surface thereof via a first adhesive layer 15, and a second thermoplastic resin film 20 laminated and bonded to the other surface of the polarizer 30 via a second adhesive layer 25.

[0120] The first adhesive layer 15 is preferably in direct contact with the first thermoplastic resin film 10. The polarizer 30 is preferably in direct contact with the first adhesive layer 15. The second adhesive layer 25 is preferably in direct contact with the second thermoplastic resin film 20. The polarizer 30 is preferably in direct contact with the second adhesive layer 25.

[0121] The polarizing plate of the present invention is preferably incorporated into an image display device so that the first thermoplastic resin film 10 side is the viewing side. That is, the optical film of the present invention is preferably a protective film laminated on the viewing side of the polarizing plate 30 .

[0122] Not limited to Figure 1 and Figure 2 For example, the polarizing plate of the present invention may include other layers (or films) other than those mentioned above. Examples of other layers include an adhesive layer laminated on the outer surface of the first thermoplastic resin film 10, the second thermoplastic resin film 20 and / or the polarizer 30; a separator (also called a "peeling film") laminated on the outer surface of the adhesive layer; a protective film (also called a "surface protection film") laminated on the outer surface of the first thermoplastic resin film 10, the second thermoplastic resin film 20 and / or the polarizer 30; an optically functional film (or layer) laminated on the outer surface of the first thermoplastic resin film 10, the second thermoplastic resin film 20 and / or the polarizer 30 via an adhesive layer or an adhesive layer.

[0123] [2] Polarizing film

[0124] The polarizer 30 is a film having the function of selectively transmitting linear polarized light in a certain direction from natural light. Examples of the polarizer 30 include an iodine-based polarizer in which iodine, which is a dichroic pigment, is adsorbed on a polyvinyl alcohol resin film and oriented, a dye-based polarizer in which a dichroic dye, which is a dichroic pigment, is adsorbed on a polyvinyl alcohol resin film and oriented, and a coating-type polarizer in which a dichroic dye in a lyotropic liquid crystal state is coated, oriented, and fixed. These polarizers selectively transmit linear polarized light in a certain direction from natural light and absorb linear polarized light in another direction, and are therefore called absorption-type polarizers.

[0125] The polarizer 30 is not limited to an absorptive polarizer, but may also be a reflective polarizer that selectively transmits linear polarized light in a certain direction from natural light and reflects linear polarized light in another direction, or a scattering polarizer that scatters linear polarized light in another direction. From the perspective of excellent visibility when the polarizing plate is applied to an image display device, etc., an absorptive polarizer is preferred.

[0126] Among them, the polarizer 30 is more preferably a polyvinyl alcohol polarizer composed of a polyvinyl alcohol resin, further preferably a polyvinyl alcohol polarizer in which a dichroic pigment such as iodine or a dichroic dye is adsorbed on a polyvinyl alcohol resin film and oriented, and particularly preferably a polyvinyl alcohol polarizer in which iodine is adsorbed on a polyvinyl alcohol resin film and oriented (polyvinyl alcohol-iodine polarizer).

[0127] The polyvinyl alcohol-based polarizing plate can be produced by a conventionally known method using a polyvinyl alcohol-based resin film (or layer).

[0128] The thickness of the polarizer 30 can be set to 30 μm or less, preferably 25 μm or less (for example, it can be 20 μm or less, further 15 μm or less, further 10 μm or less, and further 8 μm or less). The thickness of the polarizer 30 is usually 2 μm or more. Reducing the thickness of the polarizer 30 is conducive to the thinning of the polarizing plate and the image display device using the polarizing plate.

[0129] [3] Second thermoplastic resin film

[0130] The second thermoplastic resin film 20 may include a light-transmitting (preferably optically transparent) thermoplastic resin, for example, a polyolefin resin such as a chain polyolefin resin (polyethylene resin, polypropylene resin, etc.), a cyclic polyolefin resin (norbornene resin, etc.); a cellulose ester resin such as triacetyl cellulose and diacetyl cellulose; a polyester resin such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate; a polycarbonate resin; a (meth)acrylic resin, etc.

[0131] The second thermoplastic resin film 20 may be the (meth)acrylic resin film of the present invention. When the second thermoplastic resin film 20 is a (meth)acrylic resin film, the resin component constituting the second thermoplastic resin film 20 may be different from the resin component constituting the (meth)acrylic resin film of the present invention in terms of composition and the like.

[0132] The second thermoplastic resin film 20 may be an unstretched film or a uniaxially or biaxially stretched film. The biaxial stretching may be simultaneous biaxial stretching in which the film is stretched in two stretching directions at the same time, or sequential biaxial stretching in which the film is stretched in a first direction and then in a second direction different from the first direction.

[0133] The second thermoplastic resin film 20 may be a protective film that plays a role in protecting the polarizer 30, or may be a protective film that also has an optical function such as a phase difference film. For example, by stretching a film containing the above-mentioned thermoplastic resin (uniaxial stretching or biaxial stretching, etc.), or forming a liquid crystal layer on the thermoplastic resin film, etc., a phase difference film having an arbitrary phase difference value can be produced.

[0134] The second thermoplastic resin film 20 may contain additives as necessary. Examples of the additives include lubricants, anti-blocking agents, heat stabilizers, antioxidants, ultraviolet absorbers, antistatic agents, impact resistance improvers, surfactants, and mold release agents.

[0135] In one embodiment, the first thermoplastic resin film 10 is the (meth)acrylic resin film of the present invention, and the second thermoplastic resin film 20 is a polyolefin resin film (preferably a cyclic polyolefin resin film), a cellulose ester resin, or a polyester resin film.

[0136] In another embodiment, the first thermoplastic resin film 10 is the (meth)acrylic resin film of the present invention, and the second thermoplastic resin film 20 is a (meth)acrylic resin film. The (meth)acrylic resin film as the second thermoplastic resin film 20 may also be the (meth)acrylic resin film of the present invention.

[0137] The second thermoplastic resin film 20 may include a coating layer (surface treatment layer) such as a hard coat layer, an antiglare layer, an antireflection layer, a light diffusion layer, an antistatic layer, an antifouling layer, or a conductive layer on its outer surface (the surface opposite to the polarizer 30 ).

[0138] The thickness of the second thermoplastic resin film 20 is usually 5 μm or more and 200 μm or less, preferably 10 μm or more and 120 μm or less, more preferably 10 μm or more and 85 μm or less, and further preferably 15 μm or more and 65 μm or less. The thickness of the second thermoplastic resin film 20 may be 60 μm or less, or 50 μm or less. Reducing the thickness of the second thermoplastic resin film 20 is advantageous for reducing the thickness of the polarizing plate, and further, the image display device using the polarizing plate, etc.

[0139] [4] Polarizing plate manufacturing and adhesive layer

[0140] By laminating and bonding the first thermoplastic resin film 10 as the (meth)acrylic resin film of the present invention to one surface of the polarizing plate 30 via the first adhesive layer 15, it is possible to obtain Figure 1 The polarizing plate of the structure shown in the figure can be obtained by further laminating and bonding the second thermoplastic resin film 20 on the other surface of the polarizer 30 via the second adhesive layer 25. Figure 2 A polarizing plate having the structure shown.

[0141] When manufacturing a polarizing plate having both the first thermoplastic resin film 10 and the second thermoplastic resin film 20 (hereinafter, they are also collectively and simply referred to as "thermoplastic resin films"), these thermoplastic resin films may be laminated and bonded one by one in stages, or the thermoplastic resin films on both sides may be laminated and bonded simultaneously.

[0142] As the adhesive composition forming the first adhesive layer 15 and the second adhesive layer 25, there can be mentioned a water-based adhesive or an active energy ray-curable adhesive. The adhesive composition forming the first adhesive layer 15 and the adhesive composition forming the second adhesive layer 25 may be the same or different.

[0143] The adhesive used for bonding the (meth)acrylic resin film of the present invention and the polarizer is preferably an active energy ray-curable adhesive.

[0144] As the water-based adhesive, for example, a conventionally known adhesive composition using a polyvinyl alcohol resin or a urethane resin as a main component can be cited. An active energy ray-curable adhesive is an adhesive that is cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays. When an active energy ray-curable adhesive is used, the adhesive layer of the polarizing plate is a cured layer of the adhesive.

[0145] The active energy ray-curable adhesive may be an adhesive containing an epoxy compound cured by cationic polymerization as a curable component, and is preferably an ultraviolet curable adhesive containing the epoxy compound as a curable component. The epoxy compound refers to a compound having an average of one or more, preferably two or more, epoxy groups in the molecule. Only one epoxy compound may be used, or two or more epoxy compounds may be used in combination.

[0146] Examples of the epoxy compound include hydrogenated epoxy compounds (glycidyl ethers of polyols having alicyclic rings) obtained by reacting alicyclic polyols obtained by hydrogenating aromatic rings of aromatic polyols with epichlorohydrin; aliphatic epoxy compounds such as polyglycidyl ethers of aliphatic polyols or alkylene oxide adducts thereof; and alicyclic epoxy compounds which are epoxy compounds having one or more epoxy groups bonded to an alicyclic ring in the molecule.

[0147] The active energy ray-curable adhesive may contain a radically polymerizable (meth)acrylic compound as a curable component instead of the epoxy compound or together with the epoxy compound. Examples of the (meth)acrylic compound include (meth)acrylic acid ester monomers having one or more (meth)acrylic acid ester groups in the molecule; (meth)acrylic acid ester oligomers having at least two (meth)acrylic acid ester groups in the molecule obtained by reacting two or more functional group-containing compounds, and other (meth)acrylic acid ester oligomers having at least two (meth)acrylic acid ester groups in the molecule.

[0148] When the active energy ray-curable adhesive contains an epoxy compound that cures by cationic polymerization as a curable component, it is preferred to contain a photocationic polymerization initiator. Examples of the photocationic polymerization initiator include aromatic diazonium salts; aromatic iodonium salts, aromatic sulfonium salts and other onium salts; and iron-arene complexes.

[0149] When the active energy ray-curable adhesive contains a radical polymerizable component such as a (meth)acrylic compound, it is preferable to contain a photoradical polymerization initiator. Examples of the photoradical polymerization initiator include acetophenone-based initiators, benzophenone-based initiators, benzoin ether-based initiators, thioxanthone-based initiators, xanthone, fluorenone, camphorquinone, benzaldehyde, anthraquinone, and the like.

[0150] The bonding of the polarizer 30 and the thermoplastic resin film may include the following steps: applying an adhesive composition on the bonding surface of the polarizer 30 and / or the bonding surface of the thermoplastic resin film, or injecting an adhesive composition between the polarizer 30 and the thermoplastic resin film, overlapping the two films via a layer of the adhesive composition, and bonding them by pressing from top and bottom using, for example, a bonding roller.

[0151] In the formation of the adhesive composition layer, various coating methods such as scraper, wire rod, die coater, comma coater, gravure coater, etc. can be utilized. In addition, it can also be a method of continuously supplying the polarizer 30 and the thermoplastic resin film with the bonding surface of the two becoming the inner side, while casting the adhesive composition therebetween.

[0152] Before applying the adhesive composition, one or both of the bonding surfaces of the polarizer 30 and the thermoplastic resin film may be subjected to an adhesion-facilitating treatment (surface activation treatment) such as saponification treatment, corona discharge treatment, plasma treatment, flame treatment, primer treatment, anchor coating treatment, etc.

[0153] When an active energy ray-curable adhesive is used, the adhesive composition layer is cured by irradiating the adhesive composition layer with active energy rays.

[0154] The light source for irradiating the active energy ray can be any light source capable of generating ultraviolet rays, electron beams, X-rays, etc. Particularly suitable are low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, etc., which have a light emission distribution at a wavelength of 400 nm or less.

[0155] In the polarizing plate, the thickness of the first adhesive layer 15 and the second adhesive layer 25 is, for example, 0.1 μm or more and 100 μm or less, preferably 0.5 μm or more and 80 μm or less, more preferably 1 μm or more and 60 μm or less, and further preferably 2 μm or more and 50 μm or less. From the viewpoint of thinning the polarizing plate, it is also preferred that the thickness of the adhesive layer is set to 30 μm or less, and further preferably 20 μm or less. When a water-based adhesive is used, the thickness of the adhesive layer may be less than the above thickness.

[0156] The thickness of the first adhesive layer 15 and the second adhesive layer 25 may be the same or different.

[0157] [5] Other components of polarizing plates

[0158] [5-1] Optical functional films

[0159] The polarizing plate may include other optically functional films other than the polarizing plate 30 for imparting a desired optical function, and a suitable example thereof is a retardation film.

[0160] As described above, the second thermoplastic resin film 20 may also serve as a phase difference film, but a phase difference film may be laminated separately from the thermoplastic resin film. In the latter case, the phase difference film may be laminated on the outer surface of the second thermoplastic resin film 20 via an adhesive layer or a bonding agent layer. In addition, a phase difference film may be laminated instead of the second thermoplastic resin film 20. When giving a specific example, for example, Figure 1 The single-sided protective polarizing plate shown has a configuration in which the first thermoplastic resin film 10 is bonded to one surface of the polarizer 30 and a retardation film is bonded to the other surface of the polarizer 30. In this case, the retardation film may be laminated on the surface of the polarizer 30 via a pressure-sensitive adhesive layer or an adhesive layer.

[0161] Examples of the retardation film include a birefringent film composed of a stretched film of a light-transmitting thermoplastic resin; a film in which a discotic liquid crystal or a nematic liquid crystal is fixedly oriented; and a film in which the above-mentioned liquid crystal layer is formed on a base film.

[0162] The base film is generally a film made of a thermoplastic resin, and an example of the thermoplastic resin is a cellulose ester resin such as triacetyl cellulose.

[0163] As the thermoplastic resin forming the birefringent film, the thermoplastic resin described for the second thermoplastic resin film 20 can be used.

[0164] Examples of other optically functional films (optical members) that may be included in the polarizing plate include a light-collecting plate, a brightness enhancement film, a reflective layer (reflective film), a semi-transmissive reflective layer (semi-transmissive reflective film), a light diffusion layer (light diffusion film), etc. These are usually provided in the case of a polarizing plate configured on the back side (backlight side) of a liquid crystal cell.

[0165] [5-2] Adhesive layer

[0166] The polarizing plate of the present invention may include an adhesive layer for bonding the polarizing plate to an image display element such as a liquid crystal cell, an organic EL element, or other optical member. Figure 1 The polarizing plate of the structure shown in the figure can be laminated on the outer surface of the polarizer 30 (the surface opposite to the first thermoplastic resin film 10 side), and Figure 2 In the polarizing plate having the structure shown, the first thermoplastic resin film 10 or the second thermoplastic resin film 20 may be laminated on the outer surface.

[0167] In a polarizing plate of a preferred embodiment, the adhesive layer is laminated on the outer surface of the second thermoplastic resin film 20, that is, the surface on the opposite side to the first thermoplastic resin film 10 side with respect to the polarizer 30. In this embodiment, when the polarizing plate is bonded to the image display element, the polarizing plate is bonded to the image display element via the adhesive layer so that the first thermoplastic resin film 10 side becomes the viewing side.

[0168] As the adhesive used in the adhesive layer, an adhesive having a base polymer of (meth)acrylic resin, silicone resin, polyester resin, polyurethane resin, polyether resin, etc. can be used. Among them, (meth)acrylic adhesives are preferred from the viewpoints of transparency, adhesive strength, reliability, weather resistance, heat resistance, reworkability, etc.

[0169] The thickness of the pressure-sensitive adhesive layer is determined based on its adhesive strength and the like, and is appropriately in the range of 1 μm to 50 μm, and is preferably in the range of 2 μm to 40 μm.

[0170] The polarizing plate may include a separator laminated on the outer surface of the adhesive layer. The separator may be a film including polyethylene resins such as polyethylene, polypropylene resins such as polypropylene, polyester resins such as polyethylene terephthalate, etc. Among them, a stretched film of polyethylene terephthalate is preferred.

[0171] The adhesive layer may contain fillers such as glass fibers, glass beads, resin beads, metal powder or other inorganic powders, pigments, colorants, antioxidants, ultraviolet absorbers, antistatic agents, etc. as needed.

[0172] [5-3] Protective film

[0173] The polarizing plate of the present invention may include a protective film for protecting its surface (thermoplastic resin film surface, polarizer surface, etc.) The protective film is peeled off together with the adhesive layer after the polarizing plate is attached to an image display element or other optical member.

[0174] In a preferred embodiment, a polarizing plate is laminated on the surface of the first thermoplastic resin film 10 which is the (meth)acrylic resin film of the present invention.

[0175] The protective film is composed of, for example, a base film and an adhesive layer laminated thereon. The above description is applicable to the adhesive layer.

[0176] The resin constituting the substrate film may be, for example, a thermoplastic resin such as polyethylene resin such as polyethylene, a polypropylene resin such as polypropylene, a polyester resin such as polyethylene terephthalate and polyethylene naphthalate, or a polycarbonate resin, and preferably a polyester resin such as polyethylene terephthalate.

[0177] Example

[0178] The present invention is described in more detail below by showing examples, but the present invention is not limited to these examples. In the examples, % and part indicating the content or usage amount are based on mass unless otherwise specified. The thickness of the film and the adhesive layer (cured layer) was measured using a digital micrometer "MH-15M" manufactured by Nikon Corporation.

[0179] <Examples 1 to 7, Comparative Examples 1 and 2>

[0180] The components shown in Tables 1 and 2 were blended in the amounts (parts by mass) shown in Tables 1 and 2, and extrusion kneaded at 240° C. to obtain pellets of a (meth)acrylic resin composition.

[0181] In Tables 1 and 2, (C) / (B) represents the ratio of the content of component (C) (the total content of components (C-1) and (C-2)) to the content of component (B). (B) / (A) represents the ratio of the content of component (B) to the content of component (A) (the total content of components (A-1) and (A-2)). (C) / (A) represents the ratio of the content of component (C) (the total content of components (C-1) and (C-2)) to the content of component (A) (the total content of components (A-1) and (A-2)).

[0182] <Measurement and evaluation>

[0183] (1) Mass reduction rate of (meth)acrylic resin composition (heating test I)

[0184] Accurately weigh about 500 mg of sample from the prepared pellets. Place the accurately weighed sample in an accurately weighed combustion boat (No.5, ASONE product number: 2-962-03, size: 16mm×80mm×12mm). Set the combustion boat in a tube furnace and set a thermocouple on the sample. Perform the following heating test I: While circulating air at a flow rate of 50 mL / min in the tube furnace, adjust the temperature so that the atmosphere temperature directly above the combustion boat is maintained at above 270°C and below 275°C, and heat at this temperature for 3 hours. After heating test I, cool slowly, remove the combustion boat from the tube furnace, and measure the total mass of the combustion boat and the sample.

[0185] The mass reduction rate was measured based on the following formula.

[0186] Mass reduction rate = 100 × {1 - (the above total mass after heating test I - the mass of the combustion boat) / the mass of the sample before heating test I}

[0187] (2) IR intensity ratio of (meth)acrylic resin composition (heating test I)

[0188] For the sample after the heating test I, an IR spectrum was obtained using a Fourier transform infrared spectrophotometer (“Cary 660 FTIR” manufactured by Agilent Technologies Co., Ltd.). The wave number 1785±5 cm -1 The average intensity at wave number 1725 cm -1 The results are shown in Tables 1 and 2.

[0189] Wave number 1725cm -1 The peak intensity at is the signal intensity value at that wave number. The IR intensity ratio is expressed by the following formula.

[0190] IR intensity ratio = wave number 1785±5cm -1 Average intensity at wave number 1725 cm -1 The peak intensity at

[0191] [Table 1]

[0192]

[0193] [Table 2]

[0194]

[0195] <Examples 8 to 13>

[0196] Among the components shown in Table 3, the components other than the antioxidant were blended in the amounts (parts by mass) shown in Table 3, and extrusion kneaded at 240° C. to obtain pellets. Then, a predetermined amount of antioxidant (C-1) and / or (C-2) was mixed with the pellets to obtain a (meth)acrylic resin composition (mixed pellets) which was a mixture of the pellets and the antioxidant.

[0197] In Table 3, (C) / (B) represents the ratio of the content of component (C) (the total content of components (C-1) and (C-2)) to the content of component (B). (B) / (A) represents the ratio of the content of component (B) to the content of component (A) (the total content of components (A-1) and (A-2)). (C) / (A) represents the ratio of the content of component (C) (the total content of components (C-1) and (C-2)) to the content of component (A) (the total content of components (A-1) and (A-2)).

[0198] <Measurement and evaluation>

[0199] (1) Mass reduction rate of (meth)acrylic resin composition (heating test II)

[0200] About 10 g of sample was accurately weighed from the prepared mixed pellets. The accurately weighed sample was placed in an accurately weighed aluminum cup. The aluminum cup was placed in an oven (constant temperature dryer DX302 manufactured by Yamato Scientific Co., Ltd.). The following heating test II was performed: the oven temperature was set to 255°C, and the temperature was adjusted while heating for 6 hours in a manner that the atmosphere temperature in the oven was maintained at above 250°C and below 255°C. After heating test II, the sample was slowly cooled, the aluminum cup was removed from the oven, and the total mass of the aluminum cup and the sample was measured.

[0201] The mass reduction rate was measured based on the following formula.

[0202] Mass reduction rate = 100 × {1 - (the above total mass after heating test II - the mass of the aluminum cup) / the mass of the sample before heating test II}

[0203] (2) IR intensity ratio of (meth)acrylic resin composition (heating test II)

[0204] The IR intensity ratio was determined by the same method as in the above-mentioned “(2) IR intensity ratio of (meth)acrylic resin composition (heating test I)”.

[0205] [Table 3]

[0206]

[0207] The details of the components shown in Tables 1 to 3 are as follows.

[0208] [1] (Meth) acrylic resin (A-1): a methacrylic resin (homopolymer of methyl methacrylate) having a syndiotacticity (rr) of 76% based on triads

[0209] [2] (Meth) acrylic resin (A-2): a radical copolymer of methyl methacrylate / methyl acrylate = 97 / 3 (mass ratio) with a syndiotacticity (rr) of 48% in terms of triad

[0210] [3] Elastomer component (B): (meth)acrylic rubber particles as a (meth)acrylic multilayer polymer having a three-layer structure (first layer (innermost layer): copolymer of methyl methacrylate and methyl acrylate and allyl methacrylate (mass ratio 93.8 / 6.0 / 0.2) / second layer: copolymer of butyl acrylate and styrene and allyl methacrylate (mass ratio 80.6 / 17.4 / 2.0) / third layer (outermost layer): copolymer of methyl methacrylate and methyl acrylate (mass ratio 94 / 6))

[0211] [4] Antioxidant (C-1): "ADK STAB AO-80" (3,9-bis(2-(3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy)-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5,5)undecane, manufactured by ADEKA Corporation)

[0212] [5] Antioxidant (C-2): "ADK STAB PEP36" (3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, manufactured by ADEKA Corporation)

[0213] [6] Ultraviolet light absorber: "ADK STAB LA-31RG" (2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol], manufactured by ADEKA Co., Ltd.)

[0214] The IR intensity ratio of the (meth)acrylic resin compositions obtained in Examples 1 to 13 showed a smaller value than the IR intensity ratio of the (meth)acrylic resin compositions obtained in Comparative Examples 1 to 2, and the generation of gel when a heat load was applied was suppressed. In addition, the (meth)acrylic resin compositions obtained in Examples 1 to 13 had a low mass reduction rate due to heating and were excellent in heat resistance.

[0215] Description of Reference Numerals

[0216] 10: first thermoplastic resin film, 15: first adhesive layer, 20: second thermoplastic resin film, 25: second adhesive layer, 30: polarizing plate.

Claims

1. A (meth)acrylic resin composition comprising a (meth)acrylic resin (A), an elastomer component (B) and an antioxidant (C), The mass ratio of the content of the antioxidant (C) to the content of the elastomer component (B) is 0.006 or more and 0.2 or less.

2. The (meth)acrylic resin composition according to claim 1, wherein The content of the elastomer component (B) is 17.5 parts by mass or more based on 100 parts by mass of the (meth)acrylic resin (A).

3. The (meth)acrylic resin composition according to claim 1, wherein The content of the antioxidant (C) is 0.4 parts by mass or more and 3.5 parts by mass or less based on 100 parts by mass of the (meth)acrylic resin (A). The (meth)acrylic resin composition according to claim 1, wherein the mass reduction rate when heated in an air atmosphere at a temperature of 270° C. to 275° C. for 3 hours or in an air atmosphere at a temperature of 250° C. to 255° C. for 6 hours is 60% or less.

5. The (meth)acrylic resin composition according to claim 1, wherein The elastomer component (B) is rubber particles.

6. The (meth)acrylic resin composition according to claim 1, wherein The (meth)acrylic resin (A) includes a (meth)acrylic resin (A-1) and a (meth)acrylic resin (A-2) having syndiotacticity different from each other. The (meth)acrylic resin composition according to claim 1 , which is in the form of pellets. 8 . A film formed from the (meth)acrylic resin composition according to claim 1 . 9 . A polarizing plate comprising a polarizer, an adhesive layer, and the film according to claim 8 in this order.

Citation Information

Patent Citations

  • Polarizer, polarization plate, optical film and image display apparatus

    JP2008102274A

  • Set of polarizing plates and liquid crystal panel and liquid crystal display device using the same

    JP2009145397A

  • Methacrylic resin composition, molded body, and method for producing methacrylic resin composition

    JP2021155698A